RANCANG BANGUN BURNER STOVE BERBAHAN BAKAR OLI BEKAS SEBAGAI SUMBER PANAS PADA ALAT PENGERING BIJI KOPI - M.Rizal Fauzi; Fadhli Dzil Ikram; Mietra Anggara; Amri Hidayat (Program Studi Teknik Mesin Fakultas Rekayasa Sistem Universitas Teknologi Sumbawa, 2026)
Waste-oil management is a critical environmental issue, as used oil is classified as hazardous and toxic (B3) waste whose volume keeps rising with the growth of motor vehicles in Indonesia. Meanwhile, coffee farmers in Dusun Punik, Batu Lanteh District, Sumbawa Regency still face difficulties in post-harvest coffee bean drying due to their dependence on sunlight and the increasingly limited supply of firewood. This study aims to design, fabricate, and test a used-oil-fueled burner stove as a heat source for a coffee bean dryer, offering a productive use for used-oil waste. The method includes a literature review, a field study, design using Autodesk Inventor, fabrication at the Mechanical Engineering Workshop of Universitas Teknologi Sumbawa, and performance testing with three test repetitions to measure drying-chamber temperature, time to reach the target temperature, and fuel consumption. The device consists of a combustion chamber made from 4-inch A283 Grade C steel pipe, a fuel tank made from 2-inch steel pipe, a support frame made from 40×40×3 mm SS400 angle iron, a 52 cm hot-air pipe, a ¼-inch valve, and a blower. Test results show the burner stove reached the target drying temperature of 50–55°C, with an average maximum temperature of 55°C, an average time to target of 17.93 minutes, and an average fuel consumption of 253.33 ml. These results indicate that using waste oil as a heat source for coffee-bean drying is a feasible, efficient, economical, and sustainable solution.